The right to spatial development for human flourishing (Transactions of the Association of European Schools of Planning, 2020)
This paper explores the literature on spatial development for people’s multifaceted well-being and the rights to the city, and argues for people’s right to live with dignity in cities. Nature and people-friendly spatial developments are fundamental to nourishing capabilities of human beings and realising their well-being. However, in reality, spatial developments are determined by legal planning and development regimes and socio-cultural discourses. These allocate different ‘claims, privileges and power rights’ to different stakeholders, and the results may not contribute to human flourishing. This paper attempts to synthesise an evaluation framework to achieve flourishing life with dignity in cities.
Keywords: Spatial development; human flourishing; right to the city